2019
DOI: 10.3390/agronomy9050249
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulant Application with a Tropical Plant Extract Enhances Corchorus olitorius Adaptation to Sub-Optimal Nutrient Regimens by Improving Physiological Parameters

Abstract: The emerging role of plant biostimulants in enhancing nutrient efficiency is important for maintaining soil fertility under sub-optimal nutrient regimens. We aimed to elucidate the morpho-physiological and biochemical effects as well as mineral composition changes of greenhouse jute (Corchorus olitorius L.) treated with a commercial vegetal-derived biostimulant from a tropical plant extract (PE; Auxym®, Italpollina, Rivoli Veronese, Italy). Plants were sprayed in weekly intervals with a solution containing 2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
55
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 46 publications
(85 reference statements)
8
55
1
1
Order By: Relevance
“…In particular, the use of polyethylene film Mater-Bi ® 1 increased P content, confronted to the control, whereas lettuce plants that were grown under Mater-Bi ® 2 exhibited higher values of K and Ca when compared to the bare soil treatment. Our results match with previous studies on the 'nutrient acquisition response' of plant-based biostimulant application on tomato [18], jute [28], and spinach [29]. In addition to the accumulation of macronutrients in leaf tissues of biostimulant-treated plants, the use of PE reduced sodium concentration in lettuce leaves by 12%, confronted to the control, which is in harmony with Carillo et al [28] findings.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In particular, the use of polyethylene film Mater-Bi ® 1 increased P content, confronted to the control, whereas lettuce plants that were grown under Mater-Bi ® 2 exhibited higher values of K and Ca when compared to the bare soil treatment. Our results match with previous studies on the 'nutrient acquisition response' of plant-based biostimulant application on tomato [18], jute [28], and spinach [29]. In addition to the accumulation of macronutrients in leaf tissues of biostimulant-treated plants, the use of PE reduced sodium concentration in lettuce leaves by 12%, confronted to the control, which is in harmony with Carillo et al [28] findings.…”
Section: Discussionsupporting
confidence: 92%
“…Our results match with previous studies on the 'nutrient acquisition response' of plant-based biostimulant application on tomato [18], jute [28], and spinach [29]. In addition to the accumulation of macronutrients in leaf tissues of biostimulant-treated plants, the use of PE reduced sodium concentration in lettuce leaves by 12%, confronted to the control, which is in harmony with Carillo et al [28] findings. This is a very important aspect, because Na causes hypertension and cardiovascular diseases [48].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this respect, low-sized molecules such as peptides and free amino acids can 207 regulate plant phenological progress upon their easy absorption through leaves and roots by 208 promoting endogenous biosynthesis of phyto-hormones [43]. Consistently, other authors 209 [17,18,31,33,44] reported that plant growth, fruit setting and yield were enhanced by the auxin-and 210 sometimes gibberellin-like activity of the mentioned biostimulants.…”
mentioning
confidence: 93%